1999
DOI: 10.1046/j.1365-2567.1999.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Acidic pH increases the avidity of FcγR for immune complexes

Abstract: SUMMARYThe interaction of immunoglobulin G (IgG) antibodies with FccR constitutes a critical mechanism through which IgG antibody effector functions are mediated. In the current work we have examined whether human neutrophil FccR exhibit pH dependence in their association with IgG. Binding assays were performed in culture medium adjusted to different pH values. It was found that the binding of either heat-aggregated human IgG (AIgG), soluble immune complexes (sIC) or IgGcoated erythrocytes (IgG-E) was markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…Studies have indicated that extracellular acidification may change the release of inflammatory mediator, and different kinds of acid at specific pH value can cause a different change[ 1 ]. Besides that, extracellular acidification also plays an important role in modulating the function of immune cells, including polymorphonuclear leukocytes, macrophages, and lymphocytes[ 2 , 12 ]. Acid-treated monocytes and macrophages produce more IL-1beta and trigger NLRP3 inflammasome activation[ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that extracellular acidification may change the release of inflammatory mediator, and different kinds of acid at specific pH value can cause a different change[ 1 ]. Besides that, extracellular acidification also plays an important role in modulating the function of immune cells, including polymorphonuclear leukocytes, macrophages, and lymphocytes[ 2 , 12 ]. Acid-treated monocytes and macrophages produce more IL-1beta and trigger NLRP3 inflammasome activation[ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the receptor used by NK cells to recognize Cryptococcus has not been described, NK cells recognize pathogens directly [29] and studies of other receptors suggest that acidic pH can increase ligand binding either by increasing the affinity of receptor and ligand interaction or by increasing the expression of the receptor. For instance, neonatal Fc receptor binds with higher affinity to the Fc portion of IgG at acidic pH, and acidic pH also increases binding of FcγRII (CD32) and FcγRIII (CD16) to immune complexes [30], [31]. Moreover, acidic pH increases expression of CD18 on neutrophils, which is involved in binding to the endothelium [32].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Lopez and colleagues (37) showed that acidic pH increases the activity of human immunoglobulin G (IgG) binding to human neutrophils, monocytes, and NK cells. Furthermore, as shown by a number of studies (38)(39)(40)(41)(42)(43), increased activity of the complement system is also observed at lower pH.…”
Section: Humoral and Nonadaptive Immune Effectsmentioning
confidence: 99%